Special effects - Robins, Deri (Irvine, CA : QEB Publishing, 2004)
Exciting ideas and suggestions will help you produce a stunning variety of images, from bubble paintings to paper craft.
Includes index
"Have fun creating your own exciting and unusual pictures"--Cover.
"Learn art"
BL 11/01/04
0812
Keywords: Art -- Technique; Artists' materials